The relationship between clinically measured hip rotational motion and shoulder biomechanics during the pitching motion. Issue 5 (September 2015) - Laudner, Kevin; Wong, Regan; Onuki, Takashi; Lynall, Robert; Meister, Keith
Abstract Objectives To examine how clinically measured hip motion is related to shoulder biomechanics during the pitching motion. Design Cross-sectional. Methods Bilateral hip rotational range of motion was measured clinically among 34 collegiate baseball pitchers. External rotation torque and maximum horizontal adduction range of motion of the throwing shoulder were measured using a three-dimensional, high speed video capture system. Results Separate standard multiple regression analyses showed that the total hip rotational range of motion of the lead leg had a significant relationship with shoulder external rotation torque during the throwing motion (r = 0.56, P = 0.003). Both lead leg hip external rotation range of motion (r = −0.39, P = 0.02) and internal rotation range of motion (r = 0.42, P = 0.009) made significant contributions to this dependent variable. Lead leg external rotation range of motion also had a significant negative relationship with shoulder horizontal adduction range of motion (r = −0.36, P = 0.04). The total rotational range of motion of the trail leg had a significant relationship with shoulder horizontal adduction range of motion (r = 0.43, P = 0.04). However, trail leg external rotation range of motion was the only significant contributor to this relationship (r = −0.35, P = 0.04). No other significant relationships were noted (r < 0.37, P > 0.11). Conclusions Our results demonstrate that altered hip rotational range of motion, measured clinically, has a direct effect on the amount of external rotation torque and horizontal adduction range of motion of the shoulder during the throwing motion.